Prevalence and continuation of breastfeeding in Cyprus: the BrEaST start in life project - Economou, Mary; Paphiti-Demetriou, I.; Kolokotroni, Ourania; Kouta, Christiana; Lambrinou, Ekaterini; Hadjigeorgiou, Eleni; Hadjiona, V.; Tryfonos, F.; Filippou, E.; Middleton, Nicos (My University, 2015)
Background.The rate of exclusive breastfeeding for the first six months of child’s life as recommended by the WHO remains relatively low even after international and national initiatives for the promotion of breastfeeding. Currently, the only data available from Cyprus are restricted to the first 48 hours from public hospitals even though as many as three quarters of all births are performed in the private sector.Methods. A consecutive sample of 568 mothers who gave birth to a healthy full-term baby during the study period (response rate 70.8%) in all public hospital and 29 (of 35) private clinics on the island completed the 14 item breastfeeding self-efficacy scale – short form and were followed up by telephone in order to estimate the prevalence of breastfeeding at the first, fourth and sixth month after delivery.Results.One in two women in public hospitals had a vaginal delivery, while in the private sector where the rate of vaginal birth did not exceed 37.3%. While initiation of breastfeeding within the first 48 hours was relatively high (85.6% private and 79.9% public sector), exclusive breastfeeding rates did not exceed 24.4% in the public and 17.3% in the private sector. Overall perceived maternal self-efficacy was only moderate at M = 3.38 (SD = 0.89) on a 5-point Likert scale and was lower in first-time mothers and mothers of higher educational attainment. Breastfeeding rates fell sharply even by the first month of birth while by the fourth month only one in three Cypriot mothers were still breastfeeding while only one in ten were exclusively breastfeeding.Conclusion Exclusive breastfeeding in Cyprus appears particularly low even while at the clinic, which causes particular concern and needs further investigation. Together with the fact that breastfeeding self-efficacy was rather low and cesarean rates rank Cyprus amongst the highest places in Europe suggests the pressing need for breastfeeding promotion interventions.
Keywords: Breastfeeding; Mothers; Caesarian; Hospital; Babies